Mothers with hypertensive disorders of pregnancy increased risk of periventricular leukomalacia in extremely preterm or extremely low birth weight infants: A propensity score analysis - Su, Zhiwen; Huang, Weiliang; Meng, Qiong; Jia, Chunhong; Shi, Bijun; Fan, Xi; Cui, Qiliang; Chen, Jingsi; Wu, Fan (Frontiers in Pediatrics, 2022)
Background: At present, the conclusions about the impact of hypertensive disorders of pregnancy (HDP) on the clinical outcomes of preterm infants are inconsistent. This study used the propensity score matching (PSM) analysis to evaluate the effect of HDP on clinical outcomes of extremely preterm or extremely low birth weight (EP/ELBW) infants. Methods: Retrospective analysis was performed on the EP/ELBW infants discharged from 26 tertiary neonatal intensive care units or died during hospitalization from 2008 to 2017, who were divided into HDP group and non-HDP group. Through the PSM method, the six covariates of sex, gestational age, birth weight, twin or multiple pregnancy, antenatal steroids administration, and conception method were matched at a ratio of 1:1, and the survival rate at discharge and the major clinical complications were made comparison between the two groups. Results: After matching the six covariates, compared with the non-HDP group, there was no significant difference in the survival rate at discharge (64% vs. 63.2%, p>0.05), the incidence of bronchopulmonary dysplasia (BPD) or moderate to severe BPD in the HDP group (58.3% vs. 54.9%, p>0.05; 5.2% vs. 6.2%, p>0.05). The incidence of periventricular leukomalacia (PVL) in the HDP group was significantly increased (5.7% vs. 1.9%, p<0.05). Conclusions: Mothers with HDP increased the risk of PVL in EP/ELBW infants, but had no significant effect on the survival rate at discharge, or the occurrence of other complications.